Laparoscopic-assisted Rectus Sheath Block as a Novel Technique is Effective and Safe: A Randomized Controlled Trial. Issue 1 (February 2017) - Miyazaki, Dai; Shichinohe, Toshiaki; Ebihara, Yuma; Kurashima, Yo; Murakami, Soichi; Noji, Takehiro; Nakamura, Toru; Tsuchikawa, Takahiro; Okamura, Keisuke; Hirano, Satoshi
Abstract : Purpose: We developed laparoscopic-assisted rectus sheath block (LRSB) as a novel technique and report on its safety and effectiveness. Methods: Patients were randomly enrolled to an LRSB or control group (n=19 each). In the LRSB group, after the umbilical wound was closed, local anesthetic was injected transcutaneous at each of 4 sites (3 cm above and below the umbilicus bilaterally) with 10 mL of 0.25% levobupivacaine, laparoscopically. The control group received conventional postoperative pain management. The primary endpoint was visual analogue scale (VAS) pain score at the end of surgery. Secondary endpoints were VAS and Prince Henry pain scale after surgery, number of administrations of analgesics, and side effects of anesthesia. Results: No significant differences in background were seen between groups. VAS at the end of surgery was significantly lower in the LRSB group than in controls ( P <0.01). VAS and Prince Henry pain scale were significantly lower in the LRSB group from soon after surgery to postoperative day 2. No complications related to LRSB were encountered. Conclusions: LRSB was particularly effective at the end of surgery and pain scores were significantly lower in the LRSB group long after surgery. Our study shows LRSB is effective and safe for laparoscopic abdominal surgery.